Existing Conditions of Gastropod Communities in Areas Affected by Nickel Mining Overburden in the Mangrove Ecosystem of Dawi-Dawi, Southeast Sulawesi - Muhammad Fajar Purnama; Slamet Budi Prayitno; Max Rudolf Muskananfola; Suryanti Suryanti (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- Nickel mining activities significantly impacted the ecological integrity of the Pomalaa coastal area in Southeast Sulawesi, particularly in the mangrove ecosystem.- The exposure of overburden waste in the mangrove ecosystem has led to the loss of important gastropod species and a decline in population of surviving species- The low population of gastropod species in nickel mining impact areas indicates extensive environmental damage caused by these activities.ABSTRACTGastropod resources in the Dawi-Dawi mangrove ecosystem, Southeast Sulawesi are greatly influenced by the input of overburden waste (sediment) from nickel mining activities. This condition has been going on for the last 2 decades and has degraded the habitat and structure of the gastropod community. The upstream connectivity (the existing nickel mining area) and the Dawi-Dawi River estuary mean that the mangrove forest (estuary) in this area is continuously affected by (massive) overburden runoff. This research was carried out in June-August in the mangrove ecosystem of Dawi-Dawi Village, Southeast Sulawesi Province. This research aims to determine the existing condition of mangrove gastropods affected by overburden. This research began by conducting initial observations in the field, to identify mangrove ecosystems affected by overburden. research stations were determined using a purposive sampling technique (targeted) and sampling gastropods using a simple random sampling method. The ecological index of the mangrove gastropod community affected by overburden shows a tendency for a medium diversity index (H'=1.81), low species richness (R=1.42), high evenness (E=1.12), and no dominance of certain species (C=0.19). The gastropod species found are typical types that make up the mangrove fauna, namely Terebralia sulcata, Terebralia palustris, Faunus ater, Telescopium telescopium, Hebra nigra, and several taxa (genus) of climbing Littoraria snails (periwinkle) which are found in the roots, stems and leaves of mangroves. The abundance of gastropods obtained was also very low, namely around 0-12 Ind./m2. At some points (rarely) schools of small snails of the type T. sulcata (5-21 Ind./m2) are sometimes found. This research shows de facto that overburden waste eliminates (survival) or reduces the diversity and richness of gastropod species (ecological index) in the mangrove ecosystem of Dawi-Dawi.